The Analysis of English Department Students’ Difficulties in Mastering Reading Text at Muhammadiyah Aceh University - Safura, Siti; Helmanda, Cut Mawar (International Journal for Educational and Vocational Studies, 2020)
Reading is not just as a simply reading but it requires a good understanding to get the meaning of the written text. Some students yet face difficulty in receiving the meaning of the text. So, the aim of this study is to analyze the difficulties faced by the English Department students in mastering reading text, especially about finding and understanding the main idea. It also studies how the students deal with their difficulties in Intensive Reading Comprehension class. To reach the goal, 10 students were taken randomly as the participants. Question sheets were distributed to the participants and also supported with interview. They helped the writer in collecting the data about the students’ difficulties.  From the gaining data, it is found that most students had problem in mastering reading text especially in understanding main idea that caused by lacking of vocabulary mastery. To deal with this problem, the students tried some ways by practicing reading aloud, having group learning, and asking the lecturer to use the appropriate technique in teaching learning reading comprehension.